Measurement of the proton structure function F 2 at low x and low Q 2 at HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Zhang, H; Bari, G; Basile, M; Bellagamba, L; et al. (1995)
We report on a measurement of the proton structure function F 2 in the range 3.5×10-5≤x≤4×10-3 and 1.5 GeV2≤Q 2≤15GeV2 at the ep collider HERA operating at a centre-of-mass energy of √s=300GeV. The rise of F 2 with decreasing x observed in the previous HERA measurements persists in this lower x and Q 2 range. The Q 2 evolution of F 2, even at the lowest Q 2 and x measured, is consistent with perturbative QCD. © 1996 Springer-Verlag.